Influence of Meteorological Parameters on Pan Evaporation at Agartala - Jhajharia, D; Agrawal, G; Sevda, M S (Journal of Agricultural Engineering, 2009)
Evaporation is one of the vital processes in the water resources planning and management. The influence of meteorological parameters such as air temperature, relative humidity, sunshine duration, vapour pressure, wet bulb temperature, number of rainy days and wind speed on pan evaporation at Agartala was examined. The linear and exponential methods were used to check the correlation between various individual meteorological parameters and pan evaporation. The multiple regression analysis was also carried out to observe the combined effect of all the meteorological parameters on pan evaporation over Agartala. The wind speed and the mean temperature were found to have positive and significant influence on pan evaporation. In case of combined effect of various meteorological parameters on pan evaporation at Agartala. the pan evaporation was affected by mean temperature, wind speed, sunshine hours and mean relative humidity.